Cinematography and Motion Tracking Techniques in Making a Video Profile for "Genteng Pancasan" Information - Fadil Yahya; Chatarina Wilma (Journal of Multimedia Trend and Technology, 2022)
The development of the world of technology is indeed very fast, especially in the field of multimedia, many companies use multimedia as advertising media content. Multimedia is a technique that combines elements of sound (audio), graphics and video or animation. The use of motion tracking and cinematography techniques in the world of promotion can be in the form of video content and company profiles. This is what prompted the company "Genteng Pancasan" to take advantage of multimedia content, namely in the form of videos as information and promotion media to introduce products more. The author seeks to help the problems in the promotion of "Genteng Pancasan" so that they can increase the selling value of their products. The result of this paper is a video prototype using cinematography and motion tracking techniques.